Pemuridan dalam Konsep Teologi Pantekosta bagi Pertumbuhan Gereja - Baskoro, Paulus Kunto (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2021)
Discipleship is the most important part of church growth. The early church, after the descent of the Holy Spirit, experienced tremendous breakthroughs. It cannot be denied that the concept of Pentecostal theology is not overemphasized. That is why this writing about a discipleship makes an effective contribution to thinking about and starting a movement for the concept of Pentecostal theology. The movement in the gifts of the Holy Spirit is indeed very extraordinary and brings great movement in the concept of Pentecostal theology. However, if it is not based on discipleship, then the church will only focus on the sparkling gifts of gifts, but cannot be firmly rooted. This research uses descriptive method, which is studying Discipleship in the Concept of Pentecostal Theology for Church Growth from the point of view of the truth of God's Word. The purpose of this discussion is to provide a new perspective on the discipleship that is the basis of church growth. In discipleship there will be a strong foundation laying on the truth of God's Word, the growth of spiritual maturity, spiritual gifts that function more optimally, the multiplication of new leaders and the church becomes strong from generation to generation. All are fully committed to the power of the Holy Spirit who will help and equip.Pemuridan menjadi bagian yang paling penting dalam sebuah pertumbuhan gereja.. Gereja mula-mula setelah peristiwa turunnya Roh Kudus, mengalami terobosan yang luar biasa. Tidak bisa dipungkiri bahwa dalam konsep teologi Pantekosta tidak terlalu ditekankan. Itu sebabnya penulisan ini tentang sebuah pemuridan memberikan kontribusi yang efektif untuk memikirkan dan memulai sebuah gerakan bagi dalam konsep teologi Pantekosta. Kegerakan dalam karunia-karunia Roh Kudus memang sangat luar biasa dan membawa kegerakan yang hebat dalam konsep teologi Pantekosta.. Namun kalau tidak didasari dengan sebuah pemuridan, maka gereja hanya fokus kepada gemerlap kehebohan karunia saja, namun tidak bisa berakar dengan kuat. Penelitian ini menggunakan metode deskritif, yaitu mempelajari tentang Pemuridan dalam Konsep Teologi Pantekosta bagi Pertumbuhan Gereja dari sudut pandang kebenaran Firman Tuhan. Tujuan pembahasan ini adalah memberikan pandangan yang baru tentang sebuah pemuridan yang menjadi dasar pertumbuhan gereja. Dalam pemuridan akan terjadi peletakan dasar yang kuat tentang kebenaran Firman Tuhan, pertumbuhan kedewasaan rohani, karunia-karunia rohani yang berfungsi lebih optimal, multiplikasi pemimpin baru dan gereja menjadi kokoh dari generasi ke generasi. Semua diserahkan sepenuhnya dalam kekuatan Roh Kudus yang akan menolong dan memperlengkapi.